(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: To evaluate the surgical outcomes of tibial fracture fixation using an intramedullary nail under fluoroscopic guidance at Thai Binh Provincial General Hospital in 2023. Methods: A cross-sectional study was conducted on 89 patients from September 2022 to March 2023 at the Department of Orthopedics and Burns, Thai Binh Provincial General Hospital. Results: The mean postoperative hospitalization duration was 3.64 ± 0.99 days. Superficial infections occurred in 3.4% of cases, with no deep infections or chronic osteomyelitis. Most patients achieved excellent surgical outcomes, bone healing, and functional recovery at rates of 93.3%, 97.8%, and 92.1%, respectively. Conclusion: The surgical fixation of tibial shaft fractures using a closed intramedullary nail with locking screws under fluoroscopic guidance resulted in excellent outcomes, a short postoperative period, and minimal complications. Bone alignment and functional recovery were correlated with the severity of the fracture.